The elementary teacher's book of lists - Muschla, Gary Robert; Muschla, Judith A.; Muschla, Erin. (San Francisco : Jossey-Bass, 2010)
'An essential reference for all elementary teachers This comprehensive resource contains useful lists on all the subjects elementary teachers need, from core content to tips on classroom management to advice for students on study skills. The lists highlight vital areas of interest including reading, writing, mathematics, science, social studies, developing social skills, developing effective study skills, and working with an inclusive classroom. 350 reproducible lists on a wealth of subjects of interest to elementary teachers Advice for setting up the classroom, interacting with parents, and making classroom modifications Tips for use with students on studying for tests, organizing homework, and taking good notes All the lists are correlated to national content standards and will be helpful as quick study aids as well as for general reference.'--
'Grades K-5'--P. [1] of cover.
Keywords: Elementary school teaching -- Handbooks, manuals, etc; Education, Elementary -- Curricula -- Handbooks, manuals, etc